2015
DOI: 10.1002/2015jc011453
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation and stoichiometric ratios of organic matter remineralization in bottom waters of the northern Gulf of Mexico during late spring and summer

Abstract: An improved extended optimum multiparameter (eOMP) analysis was applied to hydrographic (temperature and salinity), and water chemistry data, including dissolved oxygen (O2), nutrients (nitrate plus nitrite, phosphate, and silicate), dissolved inorganic carbon (DIC), and total alkalinity (TAlk) data collected during late spring and summer from 2006 to 2012 in bottom waters off the Louisiana coast, to explore the dynamics and stoichiometry of DIC production during the development and maintenance of summer hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 85 publications
(151 reference statements)
4
16
0
Order By: Relevance
“…In hypoxic bottom waters, the DIC increase resulting from denitrification was estimated to account for 1.6–20.9% (average 9.5%) of the total DIC release. Our result is similar to the finding by Xue et al (), which suggested that the bottom DIC production in the nGOM during summer resulted from the combination of aerobic organic carbon respiration (contributing ~80%) and denitrification.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In hypoxic bottom waters, the DIC increase resulting from denitrification was estimated to account for 1.6–20.9% (average 9.5%) of the total DIC release. Our result is similar to the finding by Xue et al (), which suggested that the bottom DIC production in the nGOM during summer resulted from the combination of aerobic organic carbon respiration (contributing ~80%) and denitrification.…”
Section: Resultssupporting
confidence: 92%
“…The deficit in DIN release, relative to the release of DIC and SRP from the aerobic decomposition of organic carbon (Figures e and f), also suggested the removal of DIN especially under low oxygen conditions (Nicolas Gruber, ). In the nGOM, the decomposition of organic matter generally follows the classic Redfield ratio (Huang et al, ; Xue et al, ). We thus calculated the denitrification‐induced DIN deficit (ΔN denit ) and DIC release (ΔDIC denit ) as ΔN denit = ΔDIC biol /106 × 16 − ΔDIN biol and ΔDIC denit = ΔN denit /104 × 106.…”
Section: Resultsmentioning
confidence: 99%
“…In our study region, the riverine input of NO 3 - (Table 1) is the main nitrogen source for biological uptake and we considered the average Redfield ratio of C:O 2 =106:138 to be appropriate. Although the stoichiometry of C:N may differ from the Redfield ratio (Geider and La Roche 2002;Sambrotto et al 1993), the applicability of the Redfield C:N ratio in our study region has been proved (Huang et al 2012;Xue et al 2015; also the result of this study).…”
Section: )supporting
confidence: 55%
“…In shelf seas, CO 2 efflux during a typhoon is usually much higher than that of normal weather due to combined effect of mixing or upwelling of subsurface water with high dissolved inorganic carbon (DIC; Mathis et al, 2012;Ye et al, 2017) and extreme wind speed (Huang & Imberger, 2010;Nemoto et al, 2009). Such influence can be amplified when bottom shelf waters are hypoxic and enriched with CO 2 (Cai et al, 2011;Rabalais et al, 2014;Xue et al, 2015;Yu et al, 2014). Surface pCO 2 in the hypoxic inner East China Sea shelf is predicted to increase by 312 μatm after vertical mixing based on model simulation (Chou et al, 2009), which is much higher than that observed in the South China Sea shelf (increase by 20 μatm; Ye et al, 2017).…”
Section: Introductionmentioning
confidence: 99%